THE EFFECTIVE OF AIRBORNE PRECAUTIONS GUIDELINE IN OUTPATIENT DEPARTMENT, KOH SAMUI HOSPITAL - Chaikhan, Nutcharee (Journal of MCU Nakhondhat, 2024)
This research article the objectives were 1) to compare the results of screening patients with airborne transmission diseases before and after implementing airborne precautions guideline, 2) to evaluate professional nurse's compliance with the guidelines before and after using the guidelines, 3) to evaluate professional nurse's satisfaction after using the guidelines. It is quasi - experimental research. The study sample was purposively selected and divided into 2 groups, outpatients diagnosed with airborne diseases who received treatment at the outpatient department before and after using the guidelines, there were 83 and 100 people, respectively and 14 professional nurses working in the outpatient department. Research instruments consists of guidelines to airborne precautions, patients record form, practice evaluation form according to guidelines and questionnaire on professional nurses' satisfaction with the use of airborne precautions guideline. The content validity index was 1.0. Data were analyzed using descriptive statistics and Paired Sample t - test. The results of the research revealed that after using the guidelines, the mean score of correct screening results for patients with airborne diseases increased more than before using the guidelines, with statistical significance level was 0.00. The mean score of professional nurses' compliance with guidelines after the use of guidelines increased, with statistical significance level was 0.00, and professional nurses were at a high level of satisfaction after using the guidelines ( = 4.85, S.D. = 0.18), there are operational guidelines covering the care of patients who are risk of airborne transmission, therefore, the practice should be continuously promoted.